السماع عند البصريين والكوفيين : دراسة وصفية تحليلية مقارنة - علي, عبد الرازق احمد محمد (Gezira Journal of Educational Sciences and Humanities; مجلد 20 عدد 2 (2023), 2026)
هدفت الدراسة  لبيان السماع عند أولى المدارس النحوية مدرستي البصرة والكوفة. وما قام به علماؤهما من جهد في تقعيد القواعد وضبط اللسان العربي بعد اختلاطه بالأعاجم، والمقارنة بين المدرستين، تنبعُ أهمية الدراسة من الاهتمام باللغة العربية لأنها لغة القرآن الكريم الذي يتعبد به كل مسلم مما يستوجب تجويده ، وذلك بالاعتماد على ضوابط وقواعد النحو، و معالجة الضعف الذي لحق باللغة العربية نتيجة امتزاج العرب و أهالي البلاد المفتوحة أبان الخلافة الإسلامية الراشدة بالتركيز حول السماع ودوره في تقعيد القاعدة النحوية، اتبعت الدراسة المنهج الوصفي التحليلي المقارن مبينة ما ورد من حجج وأدلة بدراسة الحالة ووصفها وتحليلها والمقارنة بين المدرستين. توصلت الدراسة إلى أن علماء المدرسة البصرية لا يعتمدون سماع أهل المدن لاختلاطهم بالأعاجم وظهور المدنية على لسانهم، كان علماء المدرسة الكوفية يحتجون بسماع أهل وسكان البوادي والمدن اختلافاً مع المدرسة البصرية. للخليل بن احمد الفراهيدي القدْح المعلّى في إرساء قواعد السماع ووضع قوانين وقواعد النحو من مشافهة البدو الخُلّص الذين لم تفسد سلائقهم ولا ألسنتهم ، فيعدُّ هو صاحب فكرة السماع، كما له دور في نشر السماع كمصدر من مصادر تقعيد القواعد وذلك لما قام به من جهد ورحيله للبوادي. أوصت الدراسة بالاهتمام بعلم النحو كعلم ترتكز عليه علوم اللغة العربية الأخرى، تعليم الناشئة بالمراحل المدرسية الأولى كيفية النطق السليم والرسم الصحيح للكلمات العربية و ضبطها، استناداً على القواعد النحوية وذلك حتى لا يكثر اللحن والوقوع في الخطأ سيما عند تلاوة الذكر الحكيم.      The study aimed to examine the concept of "al-sama'(attested linguistic usage) introduced by the earliest grammatical schools—the schools of Basra and Kufa—and the efforts exerted by their scholars to establish grammatical rules and stanardize Arabic speech after its interaction with non-Arabs, as well as to draw a comparison between the two schools. The significance of this study stems from the importance of dedication to the Arabic language, as it is the language of the holy Quran, which every Muslim uses for worship, thereby requiring its mastery. This mastery relies on the rules and principles of grammar to address the weaknesses that affected the language after Arabs intermingled with the inhabitants of the conquered lands during the era of the Rightly-guided Caliphs. The study specifically focuses on 'al-sama’ and its role in formulating grammatical rules. The study adopted the descriptive, analytical, and comparative method, illustrating the arguments and evidence by examining, describing, and analyzing the case study, and by comparing both schools. The study has concluded that scholars of the Basra school do not accept the  'sama'  of city dwellers as a valid source, due to their mixing with non-Arabs and the impact of urbanization on their speech. In contrast to the Basra school, scholars of the Kufa school accept the 'sama' of both desert Bedouins and city dwellers alike as authoritative evidence. Al-Khalil ibn Ahmad Al-Farahidi played a leading role  in establishing the foundations of 'al-sama’. He laid down the laws and rules of grammar by directly consulting the pure Bedouins, whose innate linguistic intuition and tongues remained unspoiled. Thus, he is considered the pioneer of the 'sama’ ' concept. He also played a pivotal role in promoting 'al-sama’ as a primary source for codifying grammatical rules, as a result of the immense effort he exerted during his journeys into the desert wilderness. The study recommends focusing  on grammar as a foundational science upon which other Arabic language sciences rely. It also emphasizes teaching youngsters in the early school stages the proper pronunciation, correct spelling, and accurate diacritical marking ('dabt') of Arabic words based on grammatical rules, in order to prevent the prevalence of grammatical  errors, particularly when reciting the holy Qur'an.